Complexities in diagnosis and treatment of medullary thyroid cancer. Clinical observation - E. V. Frolova; N. N. Naumova; E. V. Salautin; E. A. Volodina (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
This article discusses the etiology of sporadic and hereditary forms of medullary thyroid cancer (MTC), diagnostic criteria that allow the most accurate and accurate diagnosis and differentiate it from similar symptoms, morphological changes in MTC, which is one of the least studied due to the peculiarities of its histogenetic genesis and low frequency of treatment of the population with this a problem. MTC is often diagnosed at the time of planned hospitalization of patients for problems in a related area, but not directly related to thyroid cancer. In this article, clinical manifestations presented in a specific clinical case are investigated, markers of immunohistochemical studies are determined. This case is interesting and unusual for the duration of the patient's treatment, as well as successful surgical interventions that were aimed at removing multiple metastases. To date, the number of referrals from patients with minimal structural and functional changes in the thyroid gland is small, which indicates that the disease is often diagnosed at a later date. In the minds of a certain percentage of the population, the idea of a possible self-healing of the body is firmly fixed, which is often decisive with the progression of the disease (especially with a sharp jump in progress, for example, after a general somatic decrease in the immune response after infectious diseases, hypothermia, radiation exposure). This article is indicative in this matter – it clearly demonstrates the need for timely vigilance and care for the body, timely medical examination of the population and attentive attitude in particular to the thyroid gland.